(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The demand for rare metals in high-tech industrial productions determines their high cost on the world market. The article provides an example of the possibility of using rare earth metals for coating the plates of cutting tools in order to increase productivity.